Analisis Pola Komunikasi Digital Perbankan Melalui Fitur Instagram Reels dalam Mengedukasi Masyarakat Terkait Isu Keamanan Data Pribadi: Studi Kasus pada Bank Mandiri, BRI, BCA, BNI, dan BTN - Isna Irawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The development of digital technology has been widely utilized in various aspects of life, including the banking sector, to facilitate online transactions. However, the rapid growth of digital technology also brings negative impacts, one of which is the threat to personal data security. Social media, particularly Instagram, has become a strategic platform for banks to quickly deliver information to the public. This study aims to analyze the digital communication patterns used by five leading banks in Indonesia (Bank Mandiri, BRI, BCA, BNI, and BTN) through Instagram Reels in educating the public on personal data security issues. This research employs a qualitative method by observing Instagram Reel content uploaded by each bank over a specific period (01 January to 31 December 2024), followed by data analysis. The results indicate that most content emphasizes appealing visuals, audience-friendly language, and a narrative approach using storytelling. Additionally, collaboration with public figures and the use of specific hashtags were found to be effective in increasing reach and engagement with the audience. This study is expected to serve as a reference for corporate communication teams in the banking industry in implementing creative and informative digital communication strategies for personal data security education campaigns through Instagram Reels.